Spatial distribution of the exchangeable base ratios in the soils of the R.U.T. irrigation district (2017)
One of the more important agricultural production centers in Colombia is the R.U.T. Irrigation District, located in the Valle de Cauca. This study evaluated the spatial distribution of ratios of Ca2+, Mg2+, Na+ and K+, along with the percentage of saturation of these bases in the cation exchange capacity. 100 samples were taken at two depths to determine the EC, pH, Ca2+, Mg2+, Na+ and K+. The interpolations were made using the Geostatistical Analyst extension of ArcGis 10.3.1. The best fit semivariogram model was used, obtaining a raster surface with values of each chemical property, with which the plans were generated. The central area of the (La Union) irrigation district was more affected, with percentages of exchangeable magnesium between 40% and 75%, an inverted Ca2+/Mg2+ ratio, and a low calcium saturation percentage. The ratios were high for Mg2+/K+, normal for K+/Mg2+, high for Ca2+/K+, and broad for (Ca2+ + Mg2+)/K+, indicating a probable potassium deficiency that affected fertility. An ionic imbalance in the exchange complex was evident in the main bases of change, which may indicate degradation processes for fertility.